The Comparison of Inflammatory Cytokines (IL-6 and IL-18) and Immune Cells in Japanese Encephalitis Patients With Different Progression - Zhou, Yun; Bian, Peiyu; Du, Hong; Wang, Tao; Li, Mengyuan; Hu, Haifeng; Ye, Chuantao; Zheng, Xuyang; Zhang, Ying; Lei, Yinfeng; Jia, Zhansheng; Lian, Jianqi (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Japanese encephalitis virus (JEV) is the main cause of viral encephalitis in Asia. Nowadays, no effective and specific therapy for JE patients is available but supportive treatment. The fatality rate of JE patients is still about 30%, and more than half survivors suffered various neuropsychiatric sequelae. Thus, more attention should be paid to JE. Methods: In this study, a retrospective cohort of JE patients was collected and the general features of JE patients admitted into the Department of Infectious Diseases were analyzed. Meanwhile, the dynamic change of cytokines and immune cells in JE patients with divergent prognosis was detected and analyzed. Results: We found a mounted proportion of adult/ old patients in JE cases. The level of IL-6 and IL-18 increased in the JE patients especially in the fatal individuals. There was continuous decreased percent of CD4+ T and B cells in the severe JE patients with fatal outcome compared with the survived JE patients. Conclusions: The consistent high level of IL-6 and IL-18 in the plasm and low proportion of CD4+ T and B cells in the PBMCs might be the indicators of poor prognosis.